In the Memory of Professor Nikolai Leus (Ukrainian Journal of Ophthalmology, 2026)
Professor Nikolai F. Leus, Head of Biochemistry Laboratory of the Filatov Institute, died suddenly at the age of 76 on the 11 May, 2016.